Analyzing the relationship between learning styles (Kolb and VARK) and creativity with the academic achievement of dental students - Mahdokht Taheri; Mehran Falahchai; Mandana Javanak; Yasamin Babaee Hemmati; Mehdi Dasht Bozorgi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: One of the influential factors in students' learning is their learning styles which have the capacity to change. Furthermore, creativity is considered one of the essential cognitive features of humans. Thus, this study aimed to analyze the relationship between learning styles (Kolb and VARK) and emotional creativity with the academic achievement of dental students. MATERIALS AND METHODS: In this descriptive-analytical study, the statistical population included dental students of the third semester and above (250 persons). The data collection tools included Kolb and VARK learning style questionnaires, Averill emotional creativity questionnaire, the total Grade Point Average (GPA), and the GPA over the past two semesters of students to measure academic achievement. The data were analyzed using the measures of the descriptive (mean and standard deviation) and the inferential statistics tests including one-sample t-test, independent t-test, correlation coefficients of Pearson, and Eta squared. RESULTS: Based on Kolb and VARK learning styles, the majority of the students had accommodating learning style (64%) and read-write style (31.6%) and also were single-styled (80.4%). No significant relationship was found between the learning styles (Kolb and VARK) and creativity with academic achievement. The students scored higher than average in emotional creativity and all of its three elements. Moreover, there was a significant relationship between emotional creativity and the gender of the students (P = 0.01). Female students showed higher emotional creativity (97.26 ± 10.34) compared to the male students (94.24 ± 8.96). CONCLUSION: There was no significant relationship between learning styles and emotional creativity of the students with their academic achievement. The accommodating and read-write learning styles were more prevalent among students and they showed high emotional creativity.